Religion and Its Position in the Society: A Critical Study on Rudolf Carnap’s Thoughts - Supriyanto, Supriyanto (Journal of Al-Tamaddun, 2024)
The battle between rationalism and empiricism is a reaction arising from an attempt to have an understanding of reality. Wilhelm Dilthey’s critique of positivism gave birth to the Vienna Circle with his ideas on logical positivism or neo-positivism. This paper explains Rudolf Carnap’s, the most prominent figure, thoughts of the understanding of religious theology’s position in logical positivism. The research results state that: first, the Vienna Circle significantly contributed to the development of contemporary philosophy; second, they were based on verification-confirmation, metaphysical elimination, and combination of knowledge aspects; and third, the transcendental philosophy offered by Immanuel Kant was on which our further studies were based. Transcendental philosophy was born out of “conflict” between empiricism and rationalism.